ANALISIS ASPEK EKONOMI LAHAN PEKARANGAN (Studi Kasus di Desa Pandanwangi Kecamatan Diwek Kabupaten Jombang) - Emmy Hamidah (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Paddy fields in urban areas are gradually being used as settlements so that paddy fields are becoming increasingly narrow, as well as dry land. The only hope left for the farm was the homestead. Referring to this problem, it is necessary to examine the Analysis of Economic Aspects of Yard Land. Yard land is the land around the residence where various types of plants are planted, livestock cultivated in the yard needs to be identified and when viewed from an additional income it is necessary to use financial analysis. The aim of the research is to find out what farming is cultivated in the yard of Pandanwangi Village, Diwek District, Jombang Regency, besides that it is also to find out to what extent the yard can increase their income. The hypothesis in this study is that the yard in Pandanwangi Village, Diwek District, Jombang Regency does not have much influence on increasing the amount of income. The research method uses a descriptive method using a survey. The determination of the area was determined deliberately in Pandanwangi Village, Diwek District, Jombang Regency. How to collect primary and secondary data by using a prepared questionnaire. Determination of respondents using a simple random way as many as 20 respondents. Data analysis used tabulation, income, R/C ratio, BC ratio and t test. The results showed that the average age of the respondents was 54 years old, including those with a lot of experience and education level, most of them graduated from high school. Yard land ownership 0.123 Ha Yard land in Pandanwangi Village is widely planted with mangoes, bananas, oranges, guava and cassava. The type of fish kept in the yard in Pandanwangi Village is catfish. Most of the livestock kept are poultry, goats and buffaloes. The income received by respondents is quite large, namely IDR 1,688,690 per respondent. The largest income is obtained from crops, livestock and fisheries. The value of the R/C ratio of yard farming in Pandanwangi Village, Diwek District, Jombang Regency = 1.92, statistically the R/C ratio > 1 or yard farming in Pandanwangi Village is very profitable.